2013
DOI: 10.1002/tesj.103
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations: The TESOL Practicum as a Professional Learning Experience

Abstract: The practicum as a learning opportunity for prospective teachers of ESL or EFL remains underexplored. Most of the studies that have been documented in the TESOL practicum literature were conducted in either North America or a few Asian contexts with novice teachers. In this study the author used diaries by five Vietnamese EFL student teachers as sources of information to investigate their experiences during a 6-week practicum period. Findings show that these student teachers were strongly inclined toward the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 30 publications
3
35
0
1
Order By: Relevance
“…The necessary cooperating teacher roles, from the student teachers' perspective, are positive guidance, especially sharing experiences, reading lesson plans before teaching thoroughly, and providing more opportunities for EFL teaching, (Hudson & Nguyen, 2008). In the same vein, in the Vietnamese context, student teachers had mentioned that their cooperating teachers' feedback was vague, abstract, and confusing to them (Canh, 2014). In fact, as Yaman and Alkaç (2010) declared, student teachers always look for mentors who are ready to help and volunteer to guide them in the teaching practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The necessary cooperating teacher roles, from the student teachers' perspective, are positive guidance, especially sharing experiences, reading lesson plans before teaching thoroughly, and providing more opportunities for EFL teaching, (Hudson & Nguyen, 2008). In the same vein, in the Vietnamese context, student teachers had mentioned that their cooperating teachers' feedback was vague, abstract, and confusing to them (Canh, 2014). In fact, as Yaman and Alkaç (2010) declared, student teachers always look for mentors who are ready to help and volunteer to guide them in the teaching practice.…”
Section: Discussionmentioning
confidence: 99%
“…Student teachers are sometimes too much stressed about the way they are assessed, which might, in return, result in a poor teaching practice performance and negative evaluation by the cooperating teachers (Canh, 2014). Student teachers also complain about having a limited degree of opportunity to implement in the school, not understanding the requirements by the supervising teacher, extra workload of writing lesson plans, time limits about completing the task, inadequate/late feedback (Allen, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…When they experience the internship, it is much different from their expectations or imaginations, so they often struggle with the internships. For example, students may become more disruptive than they can anticipate, they may not be treated and recognized as real teachers in the school, and hidden teaching-related workloads -those that they have never thought of -suddenly emerge during the internship, or they have to work in harmony with peers and the mentor (Gao & Benson, 2012;Kokkinos & Stavropoulos, 2016;Le, 2014). Generally, the rich, dynamic environment of the internship appears to present preservice teachers many challenges and uncertainties through which they can develop resilience, remove their unrealistic assumptions or expectations and become familiar with real-life practices of the profession.…”
Section: Literature Review Internships and Teacher Identity Developmentmentioning
confidence: 99%
“…In the Confucian educational context of Vietnam where hierarchy is essential (Pham, 2010), their power was not as strong as their mentor's. Therefore, they had to carefully balance complying with their mentor's expectations and using their own perspectives for teaching rationally to ensure the completion of the internship, as evidence in a study by Le (2014). Regardless of using little power to negotiate teaching practices with their mentors, the narratives indicated that in the internship, preservice teachers did exercise their power on the standpoint of a teacher, through which they own stakeholders' recognition about them as teachers.…”
Section: Negotiation Processmentioning
confidence: 99%
“…However, there remains a lack of a comprehensive view of the teacher as a learner of teaching. Despite commonly studying teachers' professional learning, a number of studies look into their cultural backgrounds (e.g., Gan, 2013;Gao & Benson, 2012;Miller, 2007;Nemtchinova, 2005), while others investigate prior beliefs (e.g., Le, 2014;Mak, 2011;Ng, Nicholas, & Williams, 2010;Tang, Lee, & Chun, 2012;Yuan & Lee, 2014), emotions (e.g., Atay, 2007;Benson, 2012;Brandt, 2006;Farrell, 2008;H. T. M. Nguyen, 2010;Pillen, Beijaard, & den Brok, 2013;Trent, 2013), and professional identity (e.g., Haniford, 2010;Miller, 2007;Trent, 2011Trent, , 2013.…”
Section: Contemporary Research On L2 Teacher Learning In Light Of Thementioning
confidence: 99%